A new species of cat-eyed snake (Serpentes: Dipsadinae: Leptodeirini) from the Andes of southern Ecuador - Torres-Carvajal, Omar; Sánchez-Nivicela, Juan C.; Posse, Valentina; Celi, Elvis; Koch, Claudia (Zootaxa, 2020)
Leptodeira is one of the most widespread and taxonomically problematic snake taxa in the Americas. Here we describe a new species of Leptodeira from the Andes of southern Ecuador based on morphological and molecular data. The new species is geographically close and morphologically similar to L. ornata and L. larcorum, from which it can be distinguished by having smaller dorsal body blotches, a longer tail, and shorter spines on the hemipenial body. The shortest genetic distances between the new species and its congeners are 0.02 (16S), 0.05 (cytb), and 0.18 (ND4). The new species is restricted to the Jubones River Basin in southern Ecuador, an area of endemism for other reptile species. Our phylogenetic analysis based on mitochondrial and nuclear DNA sequence data also supports recognition of the names L. larcorum (restricted to Peru) for “L. septentrionalis larcorum”, and L. ornata for populations of “L. s. ornata” from central and eastern Panama, western Colombia, and western Ecuador. However, some samples of “L. s. ornata” from Panama and Costa Rica, as well as the new species described herein, are not included within or more closely related to L. ornata, which is sister to the clade (L. bakeri, L. ashmeadii).